The Current State and Future Outlook of the US Economy - Husain, Anwar; Mark, Ian (iRASD Journal of Economics, 2023)
The study examines the current state of the US economy after the interest rate increases implemented by the Federal Reserve from January 2022 to July 2023 to reduce the rise in inflation. Although the Federal Reserve has successfully reduced inflation during this time period, the thesis of this paper is that future interest rate increases would be damaging to the economy and result in a recession. The five key economic indicators reviewed to assess the current state of the economy are (1) national debt, (2) real GDP growth rate, (3) inflation, (4) interest rate yield curve, and (5) unemployment. The conclusion of the paper is that the US Federal Reserve would damage several components of the economy if interest rate increases continue into the future, and it would increase the likelihood of a recession. The benefit of continuing with this monetary policy would be to decrease inflation from 3% to the publicly stated target of 2%. However, costs associated with this would be significantly higher since it would result in an increase in the US national debt and annual budget deficit because the servicing costs of the debt would increase dramatically. This would have a major impact on the US economy and eventually lead to an economic downturn.